2021
DOI: 10.1029/2021ja029115
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐Based Magnetometer Response to Impacting Magnetosheath Jets

Abstract: The terrestrial bow shock is a shock front formed in front of the magnetosphere where the supersonic solar wind abruptly decelerates to subsonic velocities. Downstream of the bow shock lies a turbulent region of warm dense plasma -the magnetosheath. In the magnetosheath, localized dynamic pressure enhancements are often observed examples (Amata et al., 2011;Archer et al., 2012;Karlsson et al., 2012). These pressure enhancements have been referred by many different names, for example, plasmoids (Gunell et al., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…These HSJ‐triggered ground magnetic field oscillations is in good agreement with a recent report by Norenius et al. (2021).…”
Section: Resultssupporting
confidence: 92%
“…These HSJ‐triggered ground magnetic field oscillations is in good agreement with a recent report by Norenius et al. (2021).…”
Section: Resultssupporting
confidence: 92%
“…There is the consensus that the jets primarily appear downstream of the quasi‐parallel bow shock (Archer & Horbury, 2013 ; Plaschke et al., 2013 ; Raptis et al., 2020 ; Vuorinen et al., 2019 ). There is evidence that magnetosheath jets significantly influence the magnetopause and cause geomagnetic substorms in Earth's magnetosphere (Hietala et al., 2018 ; Norenius et al., 2021 ; Nykyri et al., 2019 ; Wang et al., 2018 ). Magnetosheath jets are therefore an important link between the SW and the magnetopause.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that jets appear more frequently behind the Qpar shock rather than the Qperp one (Raptis, Aminalragia‐Giamini, et al., 2020; Raptis, Karlsson, et al., 2020; Vuorinen et al., 2019), and typically have significant effects on the geomagnetic environment of Earth (Plaschke et al., 2018). For example, they can enhance or initiate magnetopause reconnection (Escoubet et al., 2020; Hietala et al., 2018; Ng et al., 2021; Vuorinen et al., 2021), accelerate particles (Liu et al., 2019, 2020), generate a variety of different waves in the MSH and outer magnetosphere environment (Archer et al., 2019, 2021; Katsavrias et al., 2021) and even have effects on the inner magnetosphere and ionosphere (Hietala et al., 2012; Norenius et al., 2021; Wang et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…outer magnetosphere environment (Archer et al, 2019(Archer et al, , 2021Katsavrias et al, 2021) and even have effects on the inner magnetosphere and ionosphere (Hietala et al, 2012;Norenius et al, 2021;Wang et al, 2018).…”
mentioning
confidence: 99%